2017
DOI: 10.1111/hiv.12487
|View full text |Cite
|
Sign up to set email alerts
|

Recreational drug use and chemsex among HIV‐infected in‐patients: a unique screening opportunity

Abstract: These data strongly support the use of formal screening and drug service referral pathways at the time of admission to hospital to engage HIV-positive drug users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…We also found that the slammers tended to have a job, which has been previously reported (8). The frequency of HIV infection has been very variable in the literature, ranging from 0.6% (33) to 100% (34), but our sample of slammers was in the upper range (4,8,15,31,(33)(34)(35)(36)(37). In contrast, HCV infection was less common in our sample than in the literature (8,15,31,(35)(36)(37)(38).…”
Section: Comparison With National Cases and International Literaturesupporting
confidence: 65%
“…We also found that the slammers tended to have a job, which has been previously reported (8). The frequency of HIV infection has been very variable in the literature, ranging from 0.6% (33) to 100% (34), but our sample of slammers was in the upper range (4,8,15,31,(33)(34)(35)(36)(37). In contrast, HCV infection was less common in our sample than in the literature (8,15,31,(35)(36)(37)(38).…”
Section: Comparison With National Cases and International Literaturesupporting
confidence: 65%
“…Published studies on chemsex to date have either largely focused on specific subpopulations, for example those attending designated drug services or those who are HIV positive , or relied on online or venue‐based surveys. Studies of GBMSM attending sexual health clinics have found higher rates of recreational drug use than in heterosexual men .…”
Section: Introductionmentioning
confidence: 99%
“…"SIDU" Profile and Catalysts SIDU is reported in several countries including the United Kingdom; United States; Australia; the Netherlands; France; Spain; Portugal; Thailand; Ireland; Czech Republic; Germany; Denmark; Finland and Greece (Glynn et al, 2018;Guadamuz & Boonmongkon, 2018;Hopwood, Drysdale, & Treloar, 2018;Knoops, Bakker, Van Bodegom, & Zantkuijl, 2015;Wendel, 2011). Reported prevalence figures for MSM engaging in "SIDU" range between 1% and 50% (Bourne, Reid, Hickson, Torres-Rueda, & Weatherburn, 2015;Elliot, Singh, Tyebally, Gedela, & Nelson, 2017;Frankis & Clutterbuck, 2017;Frankis, Flowers, McDaid, & Bourne, 2018;Molina et al, 2018;Power et al, 2018). In a population of HIV-positive MSM recruited through UK health clinics, Pufall et al (2018) found that a minority of MSM reported engaging in SIDU: 10.1% (any drug); 4% (multiple drugs); 6.7% (methamphetamine); 0.4% (GHB/GBL); ketamine (1.1%) and mephedrone (6.6%).…”
Section: Resultsmentioning
confidence: 99%